2016
DOI: 10.3109/08820538.2016.1141223
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Ocular Pulse Amplitude, Choroidal Thickness, and Internal Carotid Artery Doppler Ultrasound Findings in Normal Eyes

Abstract: A fair correlation was found between the OPA and subfoveal CT in healthy subjects under the age of 50.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
5
1
Order By: Relevance
“…OPA recorded by dynamic contour tonometry was lower in eyes with lower IOP, longer axial length or thinner SFCT, but not correlated with CCT, corneal curvature or anterior chamber depth in healthy participants. 39 , 40 In contrast, we found that ACV, but not axial length or SFCT, was associated with several OPA parameters of CLS. The discrepancy may stem from the differences in characteristics of the study participants and the position and mechanism for detecting ocular pulse between dynamic contour tonometry and CLS.…”
Section: Discussioncontrasting
confidence: 68%
“…OPA recorded by dynamic contour tonometry was lower in eyes with lower IOP, longer axial length or thinner SFCT, but not correlated with CCT, corneal curvature or anterior chamber depth in healthy participants. 39 , 40 In contrast, we found that ACV, but not axial length or SFCT, was associated with several OPA parameters of CLS. The discrepancy may stem from the differences in characteristics of the study participants and the position and mechanism for detecting ocular pulse between dynamic contour tonometry and CLS.…”
Section: Discussioncontrasting
confidence: 68%
“…Indeed, a study revealed a positive correlation between the ocular pulse amplitude and SFCT in patients younger than 50 years. 23 Besides, vasodilator treatments such as sildenafil induce an increase in choroidal perfusion concomitantly with an increase in choroidal thickness. 24,25 These results corroborate the hypothesis that treatments improving ophthalmic vascularization may have an increasing effect on choroidal thickness.…”
Section: Discussionmentioning
confidence: 99%
“…18,[20][21][22] Although the link between choroidal thickness and vascular supply has been so far poorly investigated, several studies suggest that eye vascularization may have an impact on choroidal thickness. [23][24][25] The aim of this pilot study was to investigate the impact of ICA stenosis on subfoveal choroidal thickness (SFCT) and explore its variation after surgical treatment by CEA.…”
Section: Introductionmentioning
confidence: 99%
“…In healthy subjects and patients with glaucoma, other studies have found that CT was independently associated with ocular perfusion pressure after adjusting for refractory errors, suggesting that CT may indirectly reflect ocular perfusion status. 20 , 21 Ocular pulse amplitude (OPA), which provides information on intraocular blood flow, is considered to be an indicator of choroidal perfusion, and Demirok et al 22 reported that OPA was strongly correlated with CT in healthy subjects ( r = 0.481, P = 0.001). Novais et al 23 used color Doppler flowmetry to measure retrobulbar blood flow, and they found a negative correlation between CT and retrobulbar arterial resistance index; these results imply that decreased choroidal blood flow could explain CT thinning in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%